A Novel Directional Antenna for Next-Generation Fare Payment System - Dong-Jin Lee; Tae-Ki An; In-June Hwang (IEEE Access, 2023)
The fare payment system for public transportation has developed from coins, paper tickets, magnetic strips, and pre-paid cards to new technologies such as Radio-Frequency Identification (RFID) and Near Field Communication (NFC). Most fare payment systems are a fusion of NFC and mobile payment. As the latest fare payment system, the studies on gate-free technology without tag action are in progress. The gate-free system has several advantages, such as improving user convenience, eliminating congestion, and preventing the spread of infectious diseases. We introduce a gate-free system using Bluetooth Low Energy (BLE) technology as the next-generation fare payment system for public transportation. We propose a smart block structure for a gate-free system and analyze the antenna for this structure. A directional antenna is required for location detection of multiple mobile terminals in the gate-free zone, and an antenna to satisfy the requirements is analyzed. A stacked air-gap patch array that satisfies BLE performance and has high directivity has been proposed within the limited smart block size. To compensate for the low bandwidth of the patch antenna, an air gap is added between the patch radiator and the ground, and the antenna gain is increased by applying a stacked patch on the patch radiator. Based on the proposed antenna and smart block, a gate-free system testbed is installed, and the testing results are presented.